Teacher Professional Development: A Sociological Study of Senior Educators’ PD Priorities in Ontario - Hardy, Ian; Wagga, Wagga (Canadian Journal of Education/Revue canadienne de l'éducation, 2009)
This study investigated senior educators’ viewpoints on teacher professional development (PD). To examine the nature and source of participants’ perspectives, the study employed Bourdieu’s notion of practice as socially constituted and contested. Interviews were conducted in southern Ontario with 24 senior Ministry officials, principals, and academics. Participants’ current and prior experiences predisposed them to support profession‐driven PD, as well as PD for systemic‐ accountability purposes. The study suggests PD policy directives for provincial foci should (a) incorporate approaches that begin with teachers’ existing knowledge and understanding, (b) address specific school circumstances, and (c) be cognizant of broader conceptions of students’ needs. Keywords: educational practice, educational reform, Bourdieu, Ontario education Cette étude porte sur les points de vue de représentants chevronnés du monde de l’éducation sur le perfectionnement professionnel (PP). Afin d’examiner la nature et l’origine des opinions des participants, l’auteur a eu recours à la notion de pratique de Bourdieu, à savoir la pratique struc‐ turée par la société et contestée par la société. Vingt‐quatre hauts fonctionnaires, directeurs et directrices d’école et universitaires du sud de l’Ontario ont été interviewés. Les expériences actuelles et antérieures des participants les prédisposaient à appuyer le PP en soi et pour des raisons systémiques (dont l’imputabilité). L’étude semble indiquer que les orientations des poli‐ tiques provinciales en matière de perfectionnement professionnel devraient : (a) incorporer des approches qui prennent pour point de départ les connaissances et la compréhension actuelles des enseignants, (b) tenir compte du contexte particulier des écoles et (c) prendre en considération des conceptions élargies des besoins des élèves. Mots clés : perfectionnement professionnel des enseignants, pratique pédagogique, réforme de l’enseignement, Bourdieu, éducation en Ontario.